Predictors of successful outcome after adrenalectomy for unilateral primary aldosteronism - Saadi, Ahmed; Bedoui, Mohamed Ali; Zaghbib, Selim; Boussaffa, Hamza; Mokaddem, Seif; Nacef, Ibtissem Ben; Ayed, Haroun; Derouiche, Amine; Khiari, Karima; Chakroun, Marouene; Ben Slama, Riadh (Frontiers in Endocrinology, 2023)
Introduction Unilateral primary aldosteronism (UPA) is the most frequent surgically curable form of endocrine hypertension. Adrenalectomy is the cornerstone of treatment for UPA, but outcomes after surgery are variable. The cause of resistant hypertension after surgery is still a matter of debate. Our aim was to investigate cure rates after surgery and to evaluate preoperative factors that might influence the surgical outcome. Methods Between 2000 and 2021, the charts of 71 Tunisian patients who underwent laparoscopic adrenalectomy for UPA were retrospectively reviewed. Preoperative medical records were collected and follow-up data (1-158 months) were registered. Antihypertensive medication doses were calculated using defined daily doses (DDD) and postoperative outcomes were assessed using the Primary Aldosteronism Surgical Outcome (PASO) criterion. Results Of 91 enrolled patients, 71 (59% women, mean age 46 years, median length of follow-up 21 months) were suitable for evaluation. Thirty-four patients (48%) had complete clinical success according to the PASO criteria. The most relevant factors associated with complete clinical success on univariate analysis were: absence of diabetes (p= 0.007), low body mass index (BMI) (p= 0.001), lower preoperative DDD (p= 0.01), preoperatively controlled blood pressure (p= 0.024), higher plasma aldosterone to renin ratio (ARR) (p= 0.001), adenoma subtyping (p <0.001) and aldosteronoma resolution score (ARS) (p= 0.002). Multivariate regression analysis showed that the major predictors of complete clinical success were absence of diabetes (OR: 5.205), a BMI < 30 (OR: 4.930), a plasma ARR > 332 (OR: 4.554) and an ARS ≥ 3 (OR: 2.056). Conclusion Complete and partial clinical response rates were achieved in respectively 48 and 43% of cases. The main predictors of complete resolution of hypertension were absence of diabetes, low BMI, high plasma ARR and high ARS. Taking these factors into account may help identify patients at risk of persistent postoperative hypertension who may require long-term surveillance and medication.